Evaluation of relationship between cytokine and chemokine levels measured by using multiplex laboratory method before and after treatment and clinical course and treatment response in rheumathoid arthritis patients receiving TNF-α blocker therapy - (:unkn) unknown (My University, 2019)
Aim: The laboratory findings are non-specific in Rheumatoid arthritis (RA). We have based our study on this idea and chose cytokinesand chemokine to evaluate ; we then tried to establish a relationship between the progress of the disease and the levels of thesemolecules before and 3-6 months after the TNF-α blocker treatment.Material and Methods: A total of 34 RA patients (28 females, 6 males) who were diagnosed with RA and received TNF-α blockertherapy were included in the study.Blood samples were drawn from the patients before the TNF-α treatment began and then in thefollowing 3rd and 6th months of the treatment.Results: The mean age of the study group is 49.15±11.03. the mean disease period is 9.77±6.29 years and the mean treatment periodis 6.88±4.33 years. 84.6% (n=22) of the study group is female and 15.4% (n=4) is male.Patients with good treatment response toTNF-α blocker treatment were younger than the patients with medium treatment response. The increase of mean hemoglobin (Hgb)levels between 0 and 6 months were statistically meaningful (both p<0.05).Conclusion: In RA patients receiving TNF-α blocker therapy. cytokine levels decreased with treatment.The relationship between IL-6and DAS28 change in the pre-treatment and 6-month period may help the clinician to show the disease activity and to guide thecourse of the disease.
Keywords: Biyoloji; Diş Hekimliği; Alerji; Anatomi ve Morfoloji; Androloji; Anestezi; Odyoloji ve Konuşma-Dil Patolojisi; Biyokimya ve Moleküler Biyoloji; Biyofizik; Biyoteknoloji ve Uygulamalı Mikrobiyoloji; Kalp ve Kalp Damar Sistemi; Hücre Biyolojisi; Klinik Nöroloji; Yoğun Bakım, Tıp; Dermatoloji; Acil Tıp; Endokrinoloji ve Metabolizma; Gastroenteroloji ve Hepatoloji; Geriatri ve Gerontoloji; Sağlık Bilimleri ve Hizmetleri; Hematoloji; İmmünoloji; Enfeksiyon Hastalıkları; Tamamlayıcı ve Entegre Tıp; Tıbbi Etik; Tıbbi İnformatik; Tıbbi Laboratuar Teknolojisi; Genel ve Dahili Tıp; Adli Tıp; Tıbbi Araştırmalar Deneysel; Mikrobiyoloji; Nörolojik Bilimler; Kadın Hastalıkları ve Doğum; Onkoloji; Göz Hastalıkları; Ortopedi; Kulak, Burun, Boğaz; Patoloji; Pediatri; Periferik Damar Hastalıkları; Fizyoloji; Temel Sağlık Hizmetleri; Psikiyatri; Halk ve Çevre Sağlığı; Radyoloji, Nükleer Tıp, Tıbbi Görüntüleme; Rehabilitasyon; Solunum Sistemi; Romatoloji; Spor Bilimleri; Cerrahi; Transplantasyon; Tropik Tıp; Üroloji ve Nefroloji; Farmakoloji ve Eczacılık; Toksikoloji